A Randomized Controlled Trial to Evaluate the Veterans' In‐home Program for Military Veterans With Traumatic Brain Injury and Their Families: Report on Impact for Family Members. Issue 6 (26th October 2015) - Moriarty, Helene; Winter, Laraine; Robinson, Keith; Piersol, Catherine Verrier; Vause‐Earland, Tracey; Iacovone, Delores Blazer; Newhart, Brian; True, Gala; Fishman, Deborah; Hodgson, Nancy; Gitlin, Laura N.
Abstract: Background: Traumatic brain injury (TBI) creates many challenges for families as well as for patients. Few intervention studies have considered both the needs of the person with TBI and his or her family and included both in the intervention process. To address this gap, we designed an innovative intervention for veterans with TBI and families—the Veterans' In‐home Program (VIP)—targeting veterans' environment, delivered in veterans' homes, and involving their families. Objectives: To determine whether the VIP is more effective than standard outpatient clinic care in improving family members' well‐being in 3 domains (depressive symptoms, burden, and satisfaction) and to assess its acceptability to family members. Design: In this randomized controlled trial, 81 dyads (veteran/family member) were randomly assigned to VIP or an enhanced usual care control condition. Randomization occurred after the baseline interview. Follow‐up interviews occurred 3‐4 months after baseline, and the interviewer was blinded to group assignment. Setting: Interviews and intervention sessions were conducted in veterans' homes or by telephone. Participants: A total of 81 veterans with TBI recruited from a Veterans Affairs (VA) polytrauma program and a key family member for each participated. Of the 81 family members, 63 completed the follow‐up interview. Intervention: The VIP, guided by the person–environment fit model, consisted of 6 home visits and 2 telephone calls delivered by occupational therapists over a 3‐ to 4‐month period. Family members were invited to participate in the 6 home sessions. Main Outcome Measures: Family member well‐being was operationally defined as depressive symptomatology, caregiver burden, and caregiver satisfaction 3‐4 months after baseline. Acceptability was operationally defined through 3 indicators. Results: Family members in the VIP showed significantly lower depressive symptom scores and lower burden scores when compared to controls at follow‐up. Satisfaction with caregiving did not differ between groups. Family members' acceptance of the intervention was high. Conclusions: VIP represents the first evidence‐based intervention that considers both the veteran with TBI and the family. VIP had a significant impact on family member well‐being and thus addresses a large gap in previous research and services for families of veterans with TBI.